Cynara cardunculus L. as a biomass and multi-purpose crop: A review of 30 years of research. (February 2018) - Gominho, Jorge; Curt, Maria Dolores; Lourenço, Ana; Fernández, Jesús; Pereira, Helena
Abstract: This review covers 30 years on cardoon ( Cynara cardunculus L.); a perennial plant adapted to the Mediterranean climate conditions of low rainfall and hot dry summers. Its potential as a non-food agricultural crop for set-aside lands and the excellent biomass production created an enthusiastic research interest in this plant and its uses. The review starts with the plant morphology, ecology and development, followed by the agricultural aspects related to crop establishment and harvest, giving the available data on the production yields by biomass component, from small research plots to large-scale plantations. The biomass components are characterized regarding anatomical, chemical and physical properties in view of their use as feedstock for the different applications. The use of Cynara biomass for energy was assessed according to its fuel properties and performance under the various processes e.g. combustion, gasification and pyrolysis. Cynara seeds contain a linoleic acid rich oil that may be processed into a biodiesel with properties similar to commercial diesel. The production of biomethane and of ethanol were also studied with promising results. Cynara was tested as a fibre source for production of pulp and paper using different delignification processes (kraft, soda, ASAM and organosolvs) with good pulp yields and adequate physical and mechanical properties. More recently, the phytochemical and pharmacological activities of different compounds extracted from Cynara biomass are also being investigated. This plant is a good candidate to be grown in the dry lands of the Mediterranean region as a perennial field crop for multi-purposes and non-conventional uses. Highlights: Cynara cardunculus was studied as a biomass crop under Mediterranean conditions. Cynara showed potential productivity under conventional agricultural procedures. Research was made to evaluate its potential for energy, pulp and phytochemicals.